The Study of Phra Maha Moggallana Enlightenment in Pacalayamana Sutta - Chandafai, Phra Somchai; Koomkrong, Viroj (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
The objectives of this article were 1) to study the attainment of Nibbana in Theravada Buddhist scriptures; and 2) to study the attainment of the enlightenment of Mahamoggallana Thera in Capalāyamāna Sutta by studying data from Theravada Buddhist scriptures and documents related, summarized, analyzed, and compiled in a descriptive style. The results showed that The enlightenment of Mahamoggallana Thera in Capalāyamāna Sutta revealed that the Buddha had shown to the Maha Moggallana eight tactics to relieve from drowsiness, namely: 1) do not meditate on the perception that causes drowsiness; 2) contemplating the teachings that has been learned; 3) One should recite the Dhamma heard and learned; 4) One should stretch the ears on both sides and use his hands to massage it; 5) One should stand up and rub his eyes with water, looking at the four directions and look up at the stars; 6) One should contemplate on the light perception; 7) One should try to walk around; and 8) sleep with overlapping feet sensible along with making a contract, setting waking up perception reminding to wake up. Mahamoggallana Thera had developed Samatha alternating with insight cultivation as taught by the Buddha and attained Arahatship on that day. It was the seventh day since he was ordained as a Bhikkhu. He was regarded as an excellent Bhikkhu with miracle power and a left great disciple of the Buddha.